Seaweed, It is an Inedible Way of Approach to Saving the Planet Together - Ibrahim, Nur Aifiah Binti (African Journal of Sciences and Traditional Medicine, 2025)
It is a school of fish waiting to be queued up and looking at several lamp posts along the way. As an Angler fish passes by and guides them to the coral reeves to their home. On their way home, they saw several standing tall and moving wavy-like. An orb of a whirlpool as the dolphin spins around by doing a twirl. Little did they know that having a seaweed over there captivated their attention. They thought it would keep them safe forever by being camouflaged and swimming still until they found their hideout underneath the rocks shaped like a cave. This paper focuses on breathing and how humans and animals experience the ecosystem by having seaweed as a companion. This paper is to bring back what nature preserves for the seaweed to prevail and enhance its adaptation further for the future in a simplified approach of using the nearer examples and do-it-yourself method for divers and home domestic nature fans.